Nepenthes putaiguneung (Nepenthaceae), a new species from highland of Sumatra, Indonesia - Metusala, Destario; Al Farishy, Dee Dee; Jebb, Matthew (Phytotaxa, 2020)
A new species of Nepenthes—Nepenthes putaiguneung—from the highlands of Sumatra (Indonesia) is described and illustrated. This new species is morphologically similar with N. Singalana from which differs in having narrowly spathulate leaves, more gracile upper pitchers with a finely ribbed peristome, lacking teeth on its inner edge, lid with a basal crest and a short tooth-like triangular appendage near the apex on the underside (not lacking such appendages), the lid glands of lower pitcher confined to the midline (not scattered evenly over the whole surface), and pedicel of lower male flowers usually with minutely short bracteole. N. putaiguneung is also similar to N. mikei but differs in having narrowly spathulate leaves with obtuse apex, lower pitcher with slender infundibulate shape below and cylindrical above, peristome of lower pitcher with short and denser distinct ribs, lid of lower and upper pitcher with a prominent glandular crest at the base of midrib, several distinct glands on the lid of lower pitcher that clustered along the midrib; and pedicel of lower male flowers that usually with minutely short bracteole.